2015
DOI: 10.1007/s11325-015-1197-8
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular subclinical dysfunction associated with myocardial deformation changes in obstructive sleep apnea patients estimated by real-time 3D speckle-tracking echocardiography

Abstract: Patients with moderate and severe OSA tended to have both LV diastolic dysfunction and abnormalities in regional systolic function with myocardial deformation changes, in spite of the normal LV ejection fraction. Myocardial strains of the LV were negatively correlated with the AHI. Rt-3DST had important clinical significance in the early evaluation of cardiac dysfunction in OSA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
1
12
0
1
Order By: Relevance
“…In other words, 3D multidirectional strain gradually and significantly reduced from mild, across moderate, to severe OSA patients. 11 Additionally, 3D longitudinal, circumferential, radial, and area strain correlated well with AHI. However, LV mass index was increasing and LV ejection fraction, as well as LV diastolic parameters, was deteriorating in the same direction-from mild to severe OSA.…”
Section: Wang Et Al 11 Investigated 3d LV Multidirectional Strain In mentioning
confidence: 83%
See 1 more Smart Citation
“…In other words, 3D multidirectional strain gradually and significantly reduced from mild, across moderate, to severe OSA patients. 11 Additionally, 3D longitudinal, circumferential, radial, and area strain correlated well with AHI. However, LV mass index was increasing and LV ejection fraction, as well as LV diastolic parameters, was deteriorating in the same direction-from mild to severe OSA.…”
Section: Wang Et Al 11 Investigated 3d LV Multidirectional Strain In mentioning
confidence: 83%
“…with OSA and revealed that 3D LV longitudinal and area strain were significantly lower in the patients with moderate and severe OSA than in the control group and patients with mild OSA, 11 whereas 3D circumferential and radial strain were significantly reduced only in patients with severe OSA in comparison with controls. It should be emphasized that severe OSA patients had significantly lower all types of 3D strain in comparison to controls or mild and moderate OSA patients.…”
Section: Wang Et Al 11 Investigated 3d LV Multidirectional Strain In mentioning
confidence: 83%
“…In 206 patients with AHI ≥ 5/h and without cardiac disease, hypertension, or diabetes, AHI was shown to be associated with higher E/e' [12]. Also, in 78 patients with obstructive sleep apnea without any comorbidities, disease severity tended to be associated with both LV diastolic dysfunction and abnormalities in regional systolic function with myocardial deformation changes, in spite of normal LV ejection fraction [13]. In a recent report of 1506 adults in the Hispanic Community Health Study/Study of Latinos ECHO-SOL Ancillary Study, greater AHI was associated cross-sectionally with subclinical markers of LV diastolic dysfunction (E/e') and LVMI [14].…”
Section: Sleep Apnea As Predictor Of Progression Of Cardiac Diastolicmentioning
confidence: 95%
“…Нет доказательств того, что ОАС само по себе связано с достоверным снижением ФВ ЛЖ у пациентов без явной сердечно-сосудистой патологии. В то же время выводы нескольких исследований свидетельствуют о связи между тяжестью ОАС и значением скорости кровотока в миокарде ЛЖ по данным тканевой допплерографии и оценки деформации миокарда (strain) -показатели систолической функции ЛЖ, которые более чувствительны, чем ФВ ЛЖ [11][12][13]. Влияние ОАС на сердце схематично представлено на рисунке 1.…”
Section: мнение по проблемеunclassified